Catalogue of Diplotaxini (Coleoptera: Scarabaeidae: Melolonthinae) of the Old World - Bezdoek, Aleš (Zootaxa, 2004)
A catalogue of all known Old World species of the tribe Diplotaxini is presented. As of 31 December 2003, 13 genera and 422 currently valid species and subspecies are recognized. Two new names are established: Apogonia burgeoni nom. nov. for A. moseri Burgeon, 1945 (nec Ritsema, 1912) and Apogonia miyakei nom. nov. for A. ovata Miyake and Yamaguchi, 1998 (nec F hraeus in Boheman, 1857). The original spelling of Apogonia saleijana Heller, 1897 is selected here as the correct one by the action of First Reviser. The following new combinations are proposed: Dichecephala moseri (Ritsema, 1912) comb. nov., D. nasalis (Karsch, 1882) comb. nov., D. somalina (Frey, 1976) comb. nov., Metagonia brunoi (Frey, 1976) comb. nov., M. kaszabi (Frey, 1974) comb. nov., M. mediocris (Kolbe, 1891) comb. nov., M. platypus (Kolbe, 1899) comb. nov., and M. platypyge (Kolbe, 1899) comb. nov. Metagonia mediocris (Kolbe, 1899) is designated here as the type species of the genus Metagonia Kolbe, 1899. A separate list of all taxa with uncertain status and nomina nuda is also given.